A new procedure for estimating the temperature and the departure of the LTE condition in a time-dependent plasma - Bredice, Fausto Osvaldo (2013)
This paper presents a method for estimating the temperature of transient plasmas and their degree of departure of the LTE condition. This method is based on the application of the Boltzmann and Saha equations on the temporal variation of the intensity of the spectral lines of the plasma, under the assumption that the plasmas at the different times where the spectra were obtained are in Local thermal Equilibrium. The method does not require the knowledge of the spectral efficiency of the spectrometer/detector, of the transition probabilities of the lines considered or the degeneracies of the upper and lower levels. Provided that the conditions of optically thin, homogeneous plasma in LTE are fulfilled, the only limiting factor to the accuracy of the method is the precision in determining the line intensity at the two temperatures Ta and Tb considered. The method also proposes a relation between plasma temperature and electron number density which could be used for determining deviations from ideal plasma conditions in Laser-Induced Breakdown Spectroscopy (LIBS) experiments.